2013
DOI: 10.1152/ajpheart.00073.2013
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-derived hyperpolarizing factor contributes to hypoxia-induced skeletal muscle vasodilation in humans

Abstract: Spilk S, Herr MD, Sinoway LI, Leuenberger UA. Endothelium-derived hyperpolarizing factor contributes to hypoxia-induced skeletal muscle vasodilation in humans. Am J Physiol Heart Circ Physiol 305: H1639 -H1645, 2013. First published September 16, 2013 doi:10.1152/ajpheart.00073.2013.-Systemic hypoxia causes skeletal muscle vasodilation, thereby preserving O 2 delivery to active tissues. Nitric oxide (NO), adenosine, and prostaglandins contribute to this vasodilation, but other factors may also play a role. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Inhibition of EET synthesis attenuated hypoxic dilatation in the forearm (Spilk et al . ). Furthermore, dilatation induced by graded hypoxia in muscle arteries and arterioles was inhibited by antagonists of EET, HETE synthesis, K Ca or K ATP channels and accompanied by graded release of EETs, but decreased production of vasoconstrictor HETE (see Frisbee et al .…”
Section: Introductionmentioning
confidence: 97%
“…Inhibition of EET synthesis attenuated hypoxic dilatation in the forearm (Spilk et al . ). Furthermore, dilatation induced by graded hypoxia in muscle arteries and arterioles was inhibited by antagonists of EET, HETE synthesis, K Ca or K ATP channels and accompanied by graded release of EETs, but decreased production of vasoconstrictor HETE (see Frisbee et al .…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, bone nodule formation by osteoblasts was reduced (−10-fold) and almost completely inhibited as a result of moderate (1–2% O 2 ) and severe (0.2% O 2 ) hypoxia, respectively (Utting et al 2006). Reduced pO 2 is a powerful stimulator for vasodilation in other vascular beds (Spilk et al 2013) and no doubt produces similar responses in the bone vascular system. In order to rapidly restore bone pO 2 , vasodilation of bone blood vessels would be the foremost response.…”
Section: Introductionmentioning
confidence: 99%
“…) and cytochrome P‐450 inhibition (∼50%: Spilk et al . ), have all been demonstrated to significantly reduce forearm vasodilatation during hypoxia. We propose that during systemic hypoxia when SnormalaO2 is reduced to ∼80%, inhibiting the normal vasodilator and hyperaemic response (typically by the order of ∼20–30%) results in a fairly small absolute change in forearm blood flow (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…, ), Spilk et al . () found that regional infusion of fluconazole (an inhibitor of cytochrome P450 2C9) in the human forearm significantly attenuates hypoxia‐induced dilatation. There is also evidence in humans that EETs can compensate for the loss of NO at rest and during exercise in humans, thus indicating potential cross‐talk between these two pathways (Hillig et al .…”
Section: Discussionmentioning
confidence: 99%